Pengaruh Fitur Customer Review dan Persepsi Risiko Terhadap Keputusan Pembelian pada Pengguna Shopee (Studi pada Mahasiswa Universitas Bandar Lampung Prodi Manajemen Angkatan 2019) - Muhammad Fadil; Farida Efriyanti (Jurnal EMT KITA, 2023)
This study aims to analyze the impact of two independent variables, customer evaluation and perceived risk, on Shopee users' purchasing decisions. These are factors that deserve attention in the digital age because they have great potential to influence consumer behavior when shopping on the Shopee platform. Research subjects include classmates from the Faculty of Economics of Bandar Lampung University, Class of 2019. The research sample used is 107 respondents and the sampling is done according to Slovin's formula to ensure the level of study. representation of the data. Collected data were analyzed by the method of coefficient of determination analysis and tested by t-test and F-test to test the research hypothesis. Research results show that customer reviews and perceived risk have a significant influence on the purchasing decision of Shopee users. These results provide valuable information for sellers on the Shopee platform so that they can better understand the importance of product quality assessments from customers and the perceived risk. influence consumers' purchasing decisions. While the results of this study provide relevant insights, the study also recognizes that there are other factors that can influence shopping behavior at Shopee. Therefore, other variables should be included in further research for a more comprehensive understanding of consumer buying behavior in the e-commerce environment.